Propùesta de reestructuración organizacional para el "Centro de apoyo social municipal de Loja", con base en las funciones del 2012 - Carrión Guerrero, Lucía Betzabè (2016)
This research has the following characteristics: descriptive, explanatory and purposeful, the theoretical foundation is supported in the theory of management by processes. The materials used have usable and technological characteristics; The method used in the development of this work was the inductive-deductive, the no-structured observation technique was used, for defining and representing the appropriate map of the processes that already exist in the “Centro de Apoyo Municipal Social de Loja”. This permitted fulfill the objectives: to identify the processes that are developed in the CASMUL and establish the structure by processes of CASMUL , then the alignment of the processes and with the strategic objectives of the City Hall was done; it is shown in the section of the processes alignment and it is the main part of the proposal of the present research work. Then, the discussion of the results was developed which permitted to draw the following important conclusions: The organic-functional Regulations of the CASMUL in 2012, determines all the activities that the staff has to do; but it does not include the tasks that all the centers must carry out which generates a value chain. The present structure of the system permits that the staff work in their functions and it also warns about an institutional procedure which is developed in a natural way. It implies a rapid transition and it does not have a big impact. The management by processes will let the CASMUL to be up dated with the last Regulation which states that all the public institutions must have a management by processes. 5 From this proposal arise the most suitable recommendations for the institution to be adopted according to the present research work.